Deindustrialization and casinos : a winning hand? - Mazar, Alissa, 1987- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"As governments increasingly legalize and expand the availability of casinos, hoping to offset the impacts of manufacturing decline through the advancement of gambling commerce, this book examines what casinos do - and do not do - for host communities in terms of economic growth. Examining the case generally made by those seeking to establish casino developments - that they offer benefits for the 'public good' - the author draws on a case study of Canada's automotive capital (Windsor, Ontario) which was a pilot site for potential further casino development in the region. The author asks whether casinos do in fact offer good jobs, revenue generation and economic diversification. A study of the benefits of casino developments that considers the question of whether they constitute a ready answer to the problems of industrial and economic decline, this volume will appeal to scholars of sociology and urban studies with interests in the gambling industry, economic sociology, the sociology of work and urban regeneration"--
Introduction -- Windsor: Ontario: A "Company Town" -- Casino Windsor: A "Grassroots" Movement and a State-Down Initiative -- Casino Windsor as a Response to NAFTA and Automotive Job Loss -- The Canadian Auto Workers, the New Democratic Party, and the Casino Industry: A Struggle over Wages -- Casino Windsor Jobs: From Opportunity to Immobility and Precarity -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Deindustrialization -- Ontario -- Windsor -- Case studies; Casinos -- Ontario -- Windsor -- Case studies; Economic development -- Ontario -- Windsor -- Case studies; Windsor (Ont.) -- Economic conditions -- Case studies; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General